Gagasan Al-Qur'an tentang Hukum Sejarah - Hasbi, Artani (SYAMIL: Jurnal Pendidikan Agama Islam (Journal of Islamic Education), 2015)
The Qur'an speaks of human beings as closely associated with the laws of history. Many verses contain a suggestion to human about the role of history. Humans have to adjust the provisions that have been established on the facts and reality that clear and complete. Conditions set by God is a "dying" for a society / nation. The people can get the victory, but also can suffer defeat. "....if you get injured (in battle), verily others (enemies) also received a similar injury. The days of the victory, We (God) shifts (the victory) among men". (Qur'an, Ali Imran, 3: 140). Qur'an as if to say: do not fancy that God's victory is a right reserved for humans, (know) the victory is natural for human rights, for anyone who has met the requirements to achieve the win according to the laws of history and in accordance with the provisions of Allah (the laws) are applied in reality, not just theory syar'i. Winning and losing is a discussion about the man with all the dynamics. Even the Qur'an highlights the human society that is more clean and pure to appear in the stage of history to win the war, despite all the engineering and deceit, intimidation and torture. The truth will still prevail. The Qur'an reminds destruction, if they are not able to take a role in the dynamics of history, and not capable of taking the minutes of the Lord in playing its historical role. Legal history will show that the community / nation who are unable to carry out the minutes of the Lord will soon sink, then counter posed other nations that have prepared themselves with superior capabilities, so as to play a historical role as a witness of human civilization. The ordinance of God shows the linkage between victory and success, if the fulfillment of the requirements and able to achieve it.